First-episode schizophrenia is associated with a reduction of HERV-K methylation in peripheral blood. (January 2019) - Mak, Monika; Samochowiec, Jerzy; Frydecka, Dorota; Pełka-Wysiecka, Justyna; Szmida, Elżbieta; Karpiński, Paweł; Sąsiadek, Maria M.; Piotrowski, Patryk; Samochowiec, Agnieszka; Misiak, Błażej
Highlights : Lower levels of HERV-K methylation were found in first-episode schizophrenia compared to controls. Multiple-episode schizophrenia patients and controls had similar levels of HERV-K methylation. Deficit and non-deficit schizophrenia patients and controls had similar levels of HERV-K methylation. There was a significant positive correlation between chlorpromazine equivalent dosage and HERV-K methylation in multiple-episode schizophrenia patients. Abstract: Human endogenous retroviruses (HERV) have been widely associated with schizophrenia etiology. Aberrant epigenetic processes may play a role in the etiology of schizophrenia. In this study, we tested whether schizophrenia patients at different stages of illness might present alterations in the levels of HERV-K methylation. We recruited 49 first-episode schizophrenia (FES) patients with 47 age- and sex-matched healthy controls (HCs), and 100 multi-episode schizophrenia (MES) patients with 50 age- and sex-matched HCs. Based on the Schedule for Deficit Schizophrenia, patients with MES were also divided into two subgroups: deficit (D-SCZ) and non-deficit schizophrenia (ND-SCZ). DNA methylation levels of HERV-K sequences were examined in peripheral blood leukocytes. We found significantly lower levels of HERV-K methylation in FES patients compared to HCs. Patients with MES and matched HCs had similar levels of HERV-K methylation. There was a significant positive correlation between chlorpromazine equivalent dosage and HERV-K methylation levels in MES patients, but not in FES individuals. No significant differences in HERV-K methylation levels between D-SCZ and ND-SCZ as well as HCs were found. Our results indicate lower HERV-K methylation levels at early stages of schizophrenia. This difference might normalize with subsequent exacerbations of schizophrenia, likely due to the effects of antipsychotics.